Determinação de distribuição de temperatura em aviário utilizando fluidodinâmica computacional e sistema de medição com arduino - Camargo, Tiago Francisconi Borges (2015)
In this work it has been proposed to analyze the temperature distribution in a poultry using computational fluid dynamics and experimentally using a measurement system with the Arduino. This measurement system was later used for validation of data obtained qualitatively and quantitatively of computer simulations. This work was carried out in a broiler building at a private farm in the state of Paraná Northwest in the city of Cianorte. Construction is installed on the east-west direction, with dimensions of 160 m long and 15 m wide within. The assessment of the spatial distribution of the air temperature (in degrees centigrade) within the contained environment was evaluated by measurement with thermoresistance sensors coupled to digital capacitive hygrometer installed in a grid pattern with spacing of 3.0 m and 25.0 m and height of 0.5 m above the ground, constituting an arrangement of 20 sampling points. The communication, processing and storage of data have been done by creating a system using the Arduino platform and the mathematical software Scilab. The lowest cost to develop this system with a large flexibility for use and the number of sensors of the same type, analog or digital was sought. Through this measurement system, also the input and output of air with temperature sensors and pressure measurements were necessary to set boundary conditions, or even a check on the consistency of theoretical data. Moreover, for meteorological measurements developed a sensor for the direction and speed of air in 2D to 5 m above the ground, which is complemented with hygrometer installed sensor and barometer. This system could obtain data every 1 minute for only one reading for each sensor. In addition to the purpose of the validation of simulation data were collected through a portable anemometer on the same local positioning of temperature and humidity sensors sampling. Computational fluid dynamics analysis was performed by ANSYS Fluent code package and mesh generator ANSYS Meshing. Using data from the equipment, correlations from literature and the data obtained by the measurements has been used on CFD package modeling capabilities equation and to obtain a solution with the purpose of predicting the temperature distribution. These data were placed in counterpoint by calculating the error between simulated data and measured visually through profiles obtained by the Scilab software. It was observed tolerable errors for the simulations in different boundary conditions employed in relation to the movement of air. After the simulation cases with the configuration used on the farm and checked the error of those cases. The boundary condition used with less error was chosen by the author to simulate cases of equipment and different arragements from the current building configuration.